High-intensity functional exercise in older adults with dementia: A systematic review and meta-analysis - Yeh, Shu-Wei; Lin, Li-Fong; Chen, Hung-Chou; Huang, Li-Kai; Hu, Chaur-Jong; Tam, Ka-Wai; Kuan, Yi-Chun; Hong, Chien-Hsiung (Clinical rehabilitation, 2021)
This study aimed to investigate the efficacy of high-intensity functional exercise among older adults with dementia. In this systematic review and meta-analysis of randomized controlled trials, we collected articles published before August 2020 from PubMed, Embase, and the Cochrane Library to evaluate the effect of high-intensity functional exercise on older adults with dementia. Primary outcomes included improvements in balance function and gait performance (speed, cadence, and stride length). The secondary outcomes included lower limb strength, activities of daily living, psychiatric well-being, depression, and cognition. Furthermore, we performed subgroup analysis with two high-intensity functional exercise programs: the Umeå program and Hauer's program. We identified 15 articles describing six trials including older adults with dementia undergoing high-intensity functional exercise or control activity. The meta-analysis indicated that high-intensity functional exercise, both in Hauer's program and in the Umeå program, significantly improved balance function (pooled standardized mean difference 0.57, 95% confidence interval 0.31-0.83). Hauer's program significantly improved gait speed, cadence, stride length, and lower limb strength. Beneficial effects on speed, cadence, and lower limb strength were retained for several months. The Umeå program facilitated activities of daily living and psychiatric well-being, with effects on activities of daily living lasting several months. In the only eligible trial, no effects on cognition were observed. Adverse effects of high-intensity functional exercise were minimal to none. High-intensity functional exercise is generally safe and is recommended for older individuals with mild or moderate dementia to provide benefits in motor performance and daily functioning.